Elementary school teachers’ developing pedagogical content knowledge and beliefs about integrated STEM education through a professional development program - Ceran, Esra (My University, 2021)
The aim of this study is to examine the pedagogical content knowledge, pedagogical beliefs, and in-class practices of elementary teachers in the process of attending a professional development course and performing integrated STEM (Science, Technology, Engineering, Mathematics) education in their classrooms. In this research, multiple case study was used as a research design. Three teachers who worked as elementary teachers in a public school in Istanbul during the semester break and spring semester of the 2018-2019 academic year participated in this research. A professional development course was developed and applied by researcher during the semester, STEM modules were developed and implemented by the teachers in the following period. Reflections were made on the practices and the researcher's support continued. Data were collected through interviews, observations, document analysis (teachers' science and mathematics autobiographies, classroom activities, visuals, assessment-evaluation tools), audio recordings and video recordings. Data analysis was performed with comparative analysis techniques. The findings of the study revealed that teachers' pedagogical beliefs and pedagogical content knowledge about STEM education changed and improved with the professional development course. As a result, teachers' practices have also changed. Teachers’ beliefs about teaching and learning STEM, the nature of the STEM disciplines and context have significant effect when examining teachers' beliefs about STEM education. Furthermore, a STEM Pedagogical Content Knowledge (STEM PCK) framework is developed based on teachers' practices. It has been revealed that teachers' orientations toward STEM education is related to all sub-elements of STEM PCK. The framework developed in this research defines STEM PCK comprehensively and reveals the relationships between the elements clearly. During the research, a change was observed in the practices of the teachers in a way that highlights the student-centered teaching approaches and the relationships between disciplines. The findings of this research found out professional development courses that consider the conditions of the institutions where teachers work can be effective in the professional development of teachers. Professional development programs can be rich and effective when they are being oriented towards in-class practice as well as theory, allow teachers to reflect, and support teachers to work collaboratively. It was concluded that the considering teachers' pedagogical content knowledge and pedagogical beliefs together with their practices was contributed significantly to the research about STEM education.

Bu çalışmanın amacı, sınıf öğretmenlerinin bir mesleki gelişim kursuna katılma ve sınıflarında FeTeMM (Fen, Teknoloji, Mühendislik, Matematik) öğretimi gerçekleştirme süreçlerinde pedagojik alan bilgilerinin ve pedagojik inançlarının ve sınıf içi pratiklerinin alt boyutları ile incelenmesidir. Bu araştırmada çoklu durum çalışması araştırma deseni olarak kullanılmıştır. Bu araştırmaya 2018-2019 akademik yılının yarıyıl tatili ve ilkbahar döneminde İstanbul’da bulunan bir devlet okulunda sınıf öğretmenliği yapan 3 öğretmen katılmıştır. Yarıyıl süresince mesleki gelişim kursu uygulanmış, devam eden dönemde ise FeTeMM modülleri öğretmenler tarafından geliştirilip uygulanmış ve uygulamalara yönelik yansıtma yapılmıştır. Bu süreçte araştırmacının desteği devam etmiştir. Çalışmanın veri kaynaklarını; mülakatlar, gözlemler, doküman analizi (öğretmenlerin fen ve matematik otobiyografileri, sınıf içi etkinlikler, görseller, ölçme- değerlendirme araçları), ses kayıtları ve video kayıtları ile veriler toplanmıştır. Veri analizi karşılaştırmalı analiz teknikleri ile yapılmıştır. Araştırmanın bulguları, öğretmenlerin FeTeMM öğretimine yönelik pedagojik inançlarının ve pedagojik alan bilgilerinin mesleki gelişim kursu ile değişip geliştiğini ortaya koymuştur. Bunun bir sonucu olarak öğretmenlerin pratikleri de değişmiştir. Ayrıca bu araştırma, öğretmenlerin FeTeMM öğretimine ilişkin inançları incelenirken, öğretmenlerin öğrenme ve öğretmenin doğasına ilişkin inançları ve FeTeMM disiplinlerinin doğasına ilişkin inançlarının yanı sıra bağlama yönelik inançlarının da önemli bir etkisi olduğunu ortaya koymuştur. Diğer yandan bu araştırmada öğretmenlerin uygulamalarına dayalı olarak FeTeMM Pedagojik Alan Bilgileri (FeTeMM/ STEM PAB) çerçevesi oluşturulmuştur. Öğretmenlerin STEM öğretimine yönelik yaklaşımlarının FeTeMM PAB’ın tüm alt ögeleri ile bağlantılı olduğu ortaya koyulmuştur. Bu araştırma kapsamında geliştirilen FeTeMM PAB çerçevesi, FeTeMM PAB’ı kapsamlı bir şekilde tanımlamakta ve ögeler arasındaki ilişkileri açıkça ortaya koymaktadır. Öğretmenlerin araştırma süresince uygulamalarında öğrenci merkezli öğretim yaklaşımları ve disiplinler arasındaki ilişkileri öne çıkaracak şekilde değişim gözlenmiştir. Bu araştırmanın bulguları, öğretmenlerin çalıştıkları kurumların koşullarını göz önüne alan, teorinin yanı sıra uygulamaya dönük ve yansıtma yapmalarına izin veren, öğretmenlerin işbirlikli çalışmasına olanak sağlayan mesleki gelişim kurslarının öğretmenlerin mesleki gelişimlerinde etkili olabileceğini ortaya koymuştur. Araştırma sonunda öğretmenlerin pedagojik alan bilgisi ve pedagojik inançlarının pratikleri ile birlikte ele alınmasının önemi vurgulanmıştır.
Keywords: bütünleşik FeTeMM/ STEM eğitimi; Education, Elementary; Eğitim, İlk; elementary teacher; integrated STEM education; mesleki gelişim programı; Öğretmenler; pedagogical belief; pedagogical content knowledge; pedagojik alan bilgisi; pedagojik inanç; professional development program sınıf öğretmeni; Teachers